Francisco Nuñez-Hernán Cortés : réflexion autour d’une rupture (1544-1546) - Elisabeth Balancy (Caravelle)
The procedure engaged in 1544 by the law graduate Núñez against H. Cortés, of whom he was the agent in Spain, enables to examine the « customer’s link » existing between the two cousins. Since this fact is quite well known today, this article makes use of the appended private correspondence to reveal the entire « procortesian » network moving in the castellan governmental councils. The proxy Núñez appears as the essential relay that speeds up the network. The geographical tearing apart which is present here, repeats itself again and again, contributing to the settlers’ dependence upon their metropolitan agent. This mediator between the centre and the far away periphery emerges as an essential figure in the mother country/colonies’ relations.